The Effects of Pineapple Fruit Extracts (Ananas comosus) on the Quality of Chemical and Microbiological-Rabbitfish (Siganus spp.) Sauce Products - Mahrus Mahrus; Agil Al Idrus; Abdul Syukur; Lalu Zulkifli (Jurnal Penelitian Pendidikan IPA, 2023)
The present work aims to study the effect of pineapple fruit extracts on the quality of Chemical and microbiological - rabbitfish sauce products. Utilizing pineapple extract can speed up the fermentation process because pineapple extract contains bromelain enzymes that will break down rabbitfish’s protein, carbohydrate, and fat molecules into simpler molecules. The research method applied involved experimental laboratory procedures. This study used a completely randomized design. The variables observed were protein, water content, acidity (pH), total microbe, total lactic acid bacteria, Escherichia coli, Staphylococcus, and taste values. The pineapple extracts and fermentation length affected sauce product quality significantly. Pineapple extracts of 15% and 12-day fermentations produced the best sauce quality, consisting of 14.18% protein content, 73.55% moisture content, and a pH of 5.26. Besides, other parameters observed were total microbes 7.8 x 104 CFU/g, total lactic acid bacteria 1, 0 x 102 CFU/g, E. coli, and Staphylococcus sp. (negative), taste value was 3.46, but consumers did not like it so much. However, these results have met the Indonesian National Standards for the product and are safe for human consumption.